Monitoring and Evaluation in Improving Teacher's Performance - Alfiah, Luthfi; Nurlaily, Nurlaily; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2023)
Monitoring and evaluation is the basis for a school in making decisions on teacher development and promotion. This research discusses the importance of monitoring and evaluation in improving teacher performance. Monitoring and evaluation is the process of monitoring and assessing the progress and success of an educational activity, especially in terms of improving teacher performance. However, teacher performance problems are often deemed not to be in line with school expectations, so monitoring and evaluation is carried out to find solutions to these problems and improve the good performance of these teachers. Teachers must have four competencies in carrying out their duties, namely: pedagogic competence, personality competence, professional competence and social competence. The benefit of this evaluation and monitoring is to find out the abilities a teacher has in carrying out his duties and implementing the programs he has planned